Pemanfaatan pewarna alami sebagai pengganti zat pewarna sintetis Rhodamin B pada es krim - Junaidi Junaidi; Syahrizal Syahrizal (Politeknik Kesehatan Kemenkes Aceh, 2020)
Background: Ice cream is a processed milk product that is made by freezing and mixing raw materials together. The making of ice cream uses additives that are developer ingredients, stabilizers and additional coloring agents.Purpose: The aim of this study was to determine the replacement of Rhodamin B as a food additive in ice cream.Method: This type of research is an experimental nature using a completely randomized design (CRD) which is a study of 3 treatments and 3 repetitions. The object of the study was ice cream which was sold by 3 ice cream vendors, with each trader taking ice cream samples. The research method is to use thin layer chromatography test followed by the development of research namely organoleptic testing and variance testing.Results: The results of the study showed that there was an influence on the acceptability of ice cream given the coloring of dragon fruit. While the color (p = 0.102) in making ice cream from durian fruit did not show a difference in acceptability in the formulations of 5%, 10%, and 15%.Conclusion: The most appropriate formulation for the acceptability of ice cream flavor is a 10% formulation with the addition of dragon fruit to the aroma, taste and texture. It is expected that consumers will be able to recognize food and beverages sold that contain Rhodamin B and for ice cream manufacturers it is better to use coloring from fruits in making ice cream so that